Hepatic arterial infusion chemotherapy combined with PD-1 inhibitors and tyrosine kinase inhibitors for unresectable hepatocellular carcinoma: A tertiary medical center experience - Luo, Laihui; Xiao, Yongqiang; Zhu, Guoqing; Huang, Aihong; Song, Shengjiang; Wang, Tao; Ge, Xian; Xie, Jin; Deng, Wei; Hu, Zhigao; Wen, Wu; Mei, Haoran; et al. (Frontiers in Oncology, 2022)
Background Unresectable hepatocellular carcinoma (u-HCC) still accounts for the majority of newly diagnosed HCC which with poor prognosis. In the era of systemic therapy, combination therapy with programmed cell death protein-1 (PD-1) inhibitors and tyrosine kinase inhibitors (TKIs) has become mainstream. Hepatic arterial infusion chemotherapy (HAIC) as a local treatment has also shown a strong anti-tumor effect. This study aimed to investigate the efficacy and safety of HAIC, PD-1 inhibitors plus TKIs for u-HCC. Methods This retrospective study included patients with initially u-HCC between October 2020 to April 2022 who had received at least one cycle of therapy with HAIC, PD-1 inhibitors plus TKIs. The primary outcome included overall response rate (ORR), the disease control rate (DCR), surgical conversion rate, progression-free survival (PFS) and treatment-related adverse events. Results A total of 145 patients were included in the study. The median treatment cycle of HAIC and PD-1 inhibitors were 3 and 4, respectively. According to the modified RECIST criteria, the best ORR was 57.2% (83/145), 9 had achieved complete response (CR), DCR was 89.7% (130/145). Median time to achieve CR or PR was 65 days. Surgical conversion rate was 18.6% (27/145), seven patients (7/27,25.9%) achieved pathological complete response (pCR). The median follow-up was 12.5 months (4.5-20 months), and the median PFS was 9.7 months. Subgroup analysis showed that Child-pugh A patients had higher DCR (92.2% vs 79.3%, p=0.041) than Child-pugh B patients, as well as increased successful conversion rate (22.4% vs 3.4%, p=0.019). Patients without vascular invasion and extrahepatic metastases showed higher PR (63.4% vs 43.3%, p<0.05) and ORR (73.2% vs 50.0%, p<0.05) than those with vascular invasion. The ORR (73.2% vs 45.5%, p<0.05) and DCR (95.1% vs 78.8%, p<0.05) were also significantly better than those of patients with extrahepatic metastases. HAIC regimen was not related to efficacy (All p>0.05). The incidence rate of grade 3/4 treatment-related AEs was 17.7% without fatal events. Conclusion The triple combination therapy of HAIC and PD-1 inhibitors plus TKIs for patients with initially unresectable HCC exhibited satisfactory efficacy with tolerable toxicity.